Experimental and theoretical study for suitability of hybrid nano enhanced phase change material for thermal energy storage applications. (July 2022) - Kalbande, Vednath P.; Fating, Ganesh; Mohan, Man; Rambhad, Kishor; Sinha, Agnivesh Kumar
Abstract: The present experiment and analytical study was carried out for suitability analysis of novel hybrid system of nano-enhanced Phase change material (PCM) for thermal energy storage applications. In this study, an experimental setup of a hybrid thermal energy storage system was fabricated. Parabolic dish solar collector was used as receiver of solar energy so as to store heat via PCM. And experimentation was conducted with selected nano enhanced PCM after comparing the heat storage capacity of various available nano-enhance PCMs from past literature. Further, the detailed comparison was carried out between pure paraffin wax and it's composite with CuO-MWCNT on the basis of their attributes like thermal conductivity, heat capacity, and useful temperature range. Results showed that nano-enhanced PCM exhibited 6.125% higher thermal conductivity than that of pure paraffin wax. It was also observed from the experimentation that time taken by nano-enhanced PCM for complete transformation from solid to liquid phase was 66.6% lower than the time taken by pure paraffin wax. This study also unveils that the hybrid system exhibited wide range of useful temperature band that is from 60 °C–180 °C which confirms its suitability for efficient space heating applications. Highlights: Hybrid nano-enhanced PCM for thermal energy storage applications. Nano-enhanced PCM systems suggest the CuO-MWCNT nanoparticle based TES system for higher heat storage capacity. The parabolic dish solar collector is best suitable for the solar-based thermal storage system. The addition of nanoparticles in paraffin wax enhances the thermal conductivity of heat storage media. Charging rate of nano-enhanced PCM is compared through charging time.